Work from home study: mental workload, gender, and calorie needs - Didin, Fatin Saffanah; Maharani, Belia Perwitasari; Mardiono, Intan (Universitas Serang Raya, 2021)
Coronavirus disease (COVID-19) pandemic has changed how to work, learn, socialize, and many business sectors applied for the Work from Home (WFH) rule. This research aims to measure workers' mental and physical workload while working from home use Rating Scale Mental Effort and the physical workload was using calorie needs. The calculation for calories needs using physical condition of participant and food consumption in a day with Lifesum Application. Participants consisted of 40 males and 40 females. The result shows that the value of mental workloads on males and females with no different significance. But the average amount of female's work and mental workload effort is higher by 9.98 than men. More than 60% of male and female workers working from home belong to the category of heavy work seen from their calorie needs. According to the number of calories remaining, more than 70% of male and female workers have an excess amount of calories that is not suitable for worker health. This study suggested that employees need to improve the work system online to reach a healthy working system both mentally and physically. The relevant company can use the suggestion of this paper result in providing workload to employees during WFH.